Global human resource development regional and country perspectives - Garavan, Thomas N.; McCarthy, Alma M.; Morley, Michael J. (Routledge studies in human resource development, 2016)
Drawing on contributions from leading academics in the field, this volume within the Routledge Series in Human Resource Development specifically focuses on Global Human Resource Development (HRD). Specifically, the volume provides an overview of 17 regions, 85 countries and includes one emerging market grouping, CIVETS. This book examines the role of the state in HRD, the relationship between HRD and the level of economic development in the country or region, the influence of foreign direct investment within the country or region, and firm-level HRD practices within countries or regions.Global Human Resource Development analyzes HRD from institutional and cross-cultural perspectives, making it possible, for the first time, to analyze trends across countries and regions and to draw conclusions about the value of institutional and cross-cultural perspectives in the HRD context. There is currently no book on the market that conceptualizes the discipline of global HRD in this way, making this a definitive book on HRD across the globe of particular interest to researchers and reflective practitioners.